Hash Value Security Improvement of PCS Password using Signed Binary Operation - Haikal Rahmadi; Ary Bayu Nurwicaksono (Department of Informatics, Universitas Diponegoro, 2024)
Convenience and security have always been inversely related requirements in data protection systems. Users want a short and simple password that is easy to remember. On the other hand, the system that is widely used in securing user data, especially passwords, is using a one-way message digest. In addition, users are also required to use complex passwords through a combination of letters, numbers, and symbols. It aims to increase security but a complex password will make it difficult for users to remember their passwords. Even though a complex password does not necessarily make it secure because it's still on a PCS which is vulnerable to hacking. Moreover, in the current development of cybersecurity science where password hacking systems are very easy to obtain and can be used by anyone to find hash value of password on PCS quickly. A preliminary test that has been carried out proves that even complex passwords can be hacked easily. This study proposes the use of a code extension system for passwords before the hashing process is carried out through two simple schemes C1 and C2 through bitwise xor and addition operators respectively. The code from the password data is mapped out of PCS by using a unique value of data. Experimental results show that the C1 scheme is able to thwart hacking attempts by 80%, while C2 is able to increase the security of alphanumeric passwords by up to 90%. The proposed method is able to make a simple but strong password system.